International responsibility and grave humanitarian crises : collective provision for human security - Peltonen, Hannes, 1978- (Global politics and the responsibility to protect, 2013)
"This book examines responsibility in grave humanitarian crises, focusing on the international community's collective responsibility to take action in such cases as genocide or ethnic cleansing. Collective responsibility highlights how we would like to see the global level primarily as something more akin to a community of peoples, rather than as a society of states in which other international and trans-national actors operate. Since the acceptance of human rights and the atrocities of the Holocaust and other genocides, we have realised that some things concern us all: a realisation that has lead to the development of the Responsibility to Protect (R2P) framework. This book focuses on understanding the international community and its collective responsibility. Unlike the research frameworks put forward in other publications on this topic, the research model developed here does not distribute the collective responsibility to particular actors; instead, it sets out how the burden should be divided among those actors responsible in order to protect human security on a global scale. This book will be of much interest to students of humanitarian intervention, the Responsibility to Protect, international law, peace and conflict studies and IR in general"--